Analisis Pengaruh Desain Antarmuka Pengguna terhadap Adopsi Aplikasi Edukasi: Studi Kasus pada Ruangguru, Skill Academy, dan Belajar dari Rumah (Kemendikbud) di Platform Pembelajaran Daring Indonesia - Ferdy Firmansyah (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2025)
The study aims to draw a relationship between User Interface (UI) design and educational app adoption in Indonesia—compared to three of the most popular online learning apps, Ruangguru, Skill Academy, and Belajar dari Rumah (Kemendikbud). Despite increasing access to education through digital transformation, adoption challenges related to UI design are still prevalent. Increasing familiarity with an app prevents user abandonment and improves the overall user experience, leading to continued adoption and usage. Qualitative findings from survey data of 200 respondents isolated ease of navigation, visual aesthetics, and app responsiveness as the three most prominent determinants of anticipated user satisfaction and adoption patterns. Quantitatively, Ruangguru and Skill Academy showed a significant influence of UI size on user satisfaction (R² = 0.620), while Belajar dari Rumah needs to improve its UI, from the results it is recommended for educational app developers to improve UI design, increase adoption rates, and maximize user satisfaction